Adjunctive role of middle meningeal artery embolization in patients with surgical treatment of unilateral chronic subdural hematoma: a systematic review and meta-analysis of randomized controlled trials - Wach, Johannes; Vychopen, Martin; Güresir, Erdem (Frontiers in Surgery, 2025)
BackgroundChronic subdural hematoma (cSDH) is a common neurological condition, with high recurrence rates after surgical evacuation, posing significant challenges for patient outcomes. Middle meningeal artery embolization (MMAE) has emerged as a potential adjunctive therapy to reduce recurrence and reoperation rates. This meta-analysis evaluates the impact of MMAE on recurrence and reoperation rates in surgically treated unilateral subdural hematoma patients.MethodsA systematic review and meta-analysis were conducted, adhering to PRISMA guidelines. Randomized controlled trials comparing surgical evacuation with and without adjunctive MMAE were included. The primary outcomes were recurrence and reoperation rates within 90 days. Pooled odds ratios (ORs) were calculated using a random-effects model. Statistical heterogeneity was assessed using the I2 statistic.ResultsTwo trials involving 965 patients met inclusion criteria. 478 patients underwent surgery with MMAE, and 487 patients underwent only surgery. MMAE reduced reoperation rates from 6.0% in controls to 2.5% in the MMAE group (OR: 0.41, 95% CI: 0.20–0.82; p = 0.01), with no significant heterogeneity (I2 = 0%). Recurrence rates were lower in the MMAE group (5.2% vs. 9.2%, OR: 0.52, 95% CI: 0.17–1.59; p = 0.25), but the difference was not statistically significant.ConclusionMMAE significantly reduces the risk of reoperation in surgically treated unilateral subdural hematoma patients and may also reduce recurrence rates. These findings support the integration of MMAE as an adjunct to surgery in selected patients.